Generation, dynamics and bifurcation of high power soliton beams in cubic-quintic nonlocal nonlinear media. (1st May 2022) - Mishra, Manoj; Kajala, Sandeep Kumar; Sharma, Mohit; Konar, Swapan; Jana, Soumendu
Abstract: This article presents the generation and propagation dynamics of a high power Gaussian soliton beam through a highly nonlocal nonlinear media having cubic-quintic nonlinearity. Solitons are also generated with lesser explored Hermite super-Gaussian, Hermite cosh-Gaussian and Hermite cosh-super-Gaussian beam profiles. The governing nonlocal nonlinear Schrödinger equation yields matching solitons analytically using variational method as well as numerically using split-step Fourier method. Linear stability analysis identifies the parametric space for stability of the solitons against small perturbation. The variation of the system parameters leads to the bifurcation of the beam beyond a critical point. A parametric zone of bifurcation is identified. Some of the solitons are bistable too. The influence of quintic nonlinearity on generation, propagation and bifurcation is highlighted.